2016
DOI: 10.1016/j.applthermaleng.2016.01.060
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the performance of natural draft dry, pre-cooled and wet cooling towers

Abstract: Highlights  Three mathematical models and the iterative algorithms were developed.  Case studies were carried out to investigate the annual performance of the towers.  The heat rejection rate and water consumption rate of the towers were compared.  The pre-cooling enhancement can go up to 46% in the hottest month.  Hybrid tower consumes 70% less water for every MW heat rejection than wet tower.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Mass of spray water taken away by the airflow per unit time is much smaller compared to the mass flow rate of spray water. Therefore, the mass flow rate of the spray water is constant [3], which means the reduction of the water flow rate by evaporation (generally 1%-3% of the water mass flow rate) is neglected in mass balance [6,16,28]. The spray water outlet temperature is equal to the spray water inlet temperature because the heat exchange between the circulating pipe and the surroundings is negligible.…”
Section: Assumptions and Simplificationsmentioning
confidence: 99%
“…Mass of spray water taken away by the airflow per unit time is much smaller compared to the mass flow rate of spray water. Therefore, the mass flow rate of the spray water is constant [3], which means the reduction of the water flow rate by evaporation (generally 1%-3% of the water mass flow rate) is neglected in mass balance [6,16,28]. The spray water outlet temperature is equal to the spray water inlet temperature because the heat exchange between the circulating pipe and the surroundings is negligible.…”
Section: Assumptions and Simplificationsmentioning
confidence: 99%
“…Habl et al [28] explored the differences of air and water as coolant for a 50 MW solar power plant located at the south of Spain and found that by using air the electricity cost increased by around 5%. He et al [29] compared three different methods to reject excess heat from a particular cooling tower located in Australia for temperatures up to 35°C: Natural dry-air draft, pre-cooled natural dry-air draft and natural wet-air draft. It was found that the natural wet-air draft approach was capable of rejecting up 3 times more heat than the dry-air approach, but at the expense of high usage of water.…”
Section: Introductionmentioning
confidence: 99%
“…The heat and mass transfer in the pre-cooled NDDCT is coupled with air flow through the tower while the air flow is determined by balancing the energy and draft equations through an iterative process [6]. The fixed variables during iteration are tower specifications and heat exchanger specifications, hot water flow rate, hot water inlet temperature, medium thickness and ambient humidity.…”
Section: Iterative Algorithmmentioning
confidence: 99%
“…Previous studies find that the performance of NDDCTs can be improved by wetted-medium evaporative pre-cooling when the ambient air is hot and dry [6][7][8]. The concept of wetted-medium pre-cooling of a NDDCT is illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation